2020
DOI: 10.21203/rs.3.rs-24587/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Preventive Strategies for Management of COVID-19 Using Natural Molecules

Abstract: The COVID19, a fatal disease by coronavirus (SARS-CoV-2) in late 2019 in China is now pandemic caused severe acute respiratory syndrome. The pandemic of COVID-19 has reached almost all regions of the world including territories with the death toll of more than 35,000. It has been estimated that one out every six-person affected by COVID-19 developed life-threatening conditions. The difficulty is that there are no vaccines or no specific treatment modalities for the management of COVID-19, apart from symptomati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…11 Our published molecular docking studies clearly indicated that curcumin can bind to the receptors and inhibit ACE2, thus blocking the entry of COVID-19 virus. 27 Vitamin K2-7 is effective in reducing pro inflammatory cytokines. Selenomethionine is a natural form of Selenium (Se) which plays a critical role in prevention of infection.…”
Section: Discussionmentioning
confidence: 99%
“…11 Our published molecular docking studies clearly indicated that curcumin can bind to the receptors and inhibit ACE2, thus blocking the entry of COVID-19 virus. 27 Vitamin K2-7 is effective in reducing pro inflammatory cytokines. Selenomethionine is a natural form of Selenium (Se) which plays a critical role in prevention of infection.…”
Section: Discussionmentioning
confidence: 99%